An experimental study on fracture process zone in HSC three point bend beam specimen using acoustic emission method - Sagar, R. Vidya; Prasad, B. K. Raghu (Journal of Structural Engineering, 2025)
An attempt has been made to experimentally investigate the fracture process zone (FPZ) using Acoustic Emission (AE) method in High Strength Concrete (HSC) beams subjected to monotonically increasing load. Stress waves are released during the fracture process in materials, which cause acoustic emissions. AE energy released during the fracture of notched HSC beam specimens during Three Point Bend (TPB) tests is measured and is used to investigate the FPZ in the notched HSC beams having 28-day compressive strength of 78.0 MPa. The specimens are tested by Material Testing System (MTS) of 1200 KN capacity employing Crack Mouth Opening Displacement (CMOD) control at the rate of 0.0004 mm/sec in accordance with RILEM recommendations. A brief review on AE technique applied to concrete fracture is presented. The fracture process zone developed and the AE energy released during the fracture process in high strength concrete beam specimens are presented and discussed. It was observed that AE events containing higher energy are located around the notch tip. It may be possible to relate AE energy to fracture energy of concrete.